Clinically relevant germline variants in allogeneic hematopoietic stem cell transplant recipients - Lahtinen Atte K.; Koski Jessica; Ritari Jarmo; Hyvärinen Kati; Koskela Satu; Partanen Jukka; Vettenranta Kim; Koskenvuo Minna; Niittyvuopio Riitta; Salmenniemi Urpu; Itälä-Remes Maija; Jahnukainen Kirsi; et al. (SPRINGERNATURE, 2022)
Allogeneic hematopoietic stem cell transplantation (HSCT) provides patients with severe hematologic disease a well-established potential for curation. Incorporation of germline analyses in the workup of HSCT patients is not a common practice. Recognizing rare harmful germline variants may however affect patients' pre-transplantation care, choice of the stem cell donor, and complication risks. We analyzed a population-based series of germline exome data of 432 patients who had undergone HSCT. Our aim was to identify clinically relevant variants that may challenge the outcome of the HSCT. We focused on genes predisposing to hematological diseases, or solid tumors, and genes included in the American College of Medical Genetics secondary findings list v3.0. As population-specific controls, we used GnomAD non-cancer Finns (n = 10,816). We identified in our population-based analysis rare harmful germline variants in disease-predisposing or actionable toxicity-increasing genes in 17.8% of adult and pediatric patients that have undergone HSCT (15.1% and 22.9%, respectively). More than half of the patients with a family member as a donor had not received genetic diagnosis prior to the HSCT. Our results encourage clinicians to incorporate germline genetic testing in the HSCT protocol in the future in order to reach optimal long-term outcome for the patients.